Correlation between partial thromboplastin time and thromboelastography in adult critically ill patients requiring bivalirudin for extracorporeal membrane oxygenation. Issue 3 (22nd February 2023) - Buckley, Mitchell S.; Benanti, Grace E.; Meckel, Jordan; Tekle, Luwam A.; Gilbert, Brian; Puebla Neira, Daniel; McNierney, Dakota A.; Korkames, Grace; Yerondopoulos, Melanie; Park, Andrew; O'Hea, Jennifer A.; MacLaren, Robert
Abstract: Study Objective: Thromboelastography (TEG) offers a more dynamic assessment of hemostasis over activated partial thromboplastin time (aPTT). However, the clinical utility of TEG in monitoring bivalirudin during extracorporeal membrane oxygenation (ECMO) remains unknown. The purpose of this study was to evaluate the correlation between aPTT and TEG in adult ECMO patients anticoagulated with bivalirudin. Design: Multicenter, retrospective, cohort study conducted over a 2‐year period. Setting: Two academic university medical centers (Banner University Medical Center) in Phoenix and Tucson, AZ. Patients: Adult patients requiring ECMO and bivalirudin therapy with ≥1 corresponding standard TEG and aPTT plasma samples drawn ≤4 h of each other were included. The primary endpoint was to determine the correlation coefficient between the standard TEG reaction (R) time and bivalirudin aPTT serum concentrations. Measurements and Main Results: A total of 104 patients consisting of 848 concurrent laboratory assessments of R time and aPTT were included. A moderate correlation between TEG R time and aPTT was demonstrated in the study population ( r  = 0.41; p < 0.001). Overall, 502 (59.2%) concurrent assessments of TEG R time and aPTT values showed agreement on whether they were sub‐, supra‐, or therapeutic according to the institution's classification for bivalirudin. The 42.2% ( n = 271/642) discordant TEG R times among "therapeutic" aPTT were almost equally distributed between subtherapeutic and supratherapeutic categories. Conclusions: Moderate correlation was found between TEG R time and aPTT associated with bivalirudin during ECMO in critically ill adults. Further research is warranted to address the optimal test to guide clinical decision‐making for anticoagulation dosing in ECMO patients.